Computer software protection in Europe and the EC Parliamentary Directive on copyright for computer software. - Magrab, E. Brendan (1992)
Examines what computer software is and why it is easily pirated or copied. Analyses the protection granted to computer software under the EC Directive for copyright protection. Concludes that the new EC Directive will benefit computer software firms, because it will provide uniform protection for computer software throughout the EC and that it will benefit consumers because the directive will permit reverse-engineering.